Smoking among women hospitalized due to reproductory organ diseases - Słopiecka, Aleksandra; Cieślik, Aleksandra (Polish Journal of Public Health, 2009)
Introduction. Smoking is one of the biggest threats to human health and life. According to JK Karczewski et al. “…more people die because of smoking than because of AIDS, alcoholism, car accidents, drugs, fi res, assassinations and suicides all together…”. The scale of the problem – the harmful effect of smoking on human health – is evidenced by the fact that every 10 seconds one person in the world dies from a smoking-related disease.Aim of the work. The study aimed at analysing smoking by women hospitalized because of diseases of the reproductive organ.Material and methods. The following variables have been analysed in detail: the fact of regular smoking; smoking start age; number of daily smoked cigarettes; period of regular smoking. A group of 210 women aged 18 to 73 was included in the study. Women participating in the study were hospitalized in gynaecology departments because of the need to diagnose and/or treat diseases of the reproductive organ (including cancers). The study was carried out in 2002 and 2003. The study was performed in four out of the total of fi ve gynaecology departments in the city of Kielce. Patients included in the study were selected at random. The study employed a survey questionnaire. Patients participated in the study on an anonymous and voluntary basis.Results. The results obtained in the study made it possible to formulate the following conclusions:1.Smoking women made up almost one third of the population under study (31.9%).2.Most women (74.6%) start smoking before 21 years of age.3.About a half of smoking women (51%) smoke more than 10 cigarettes a day.4.As regards the active smoking period, women with an 11 to 20 years’ smoking history were the most numerous group in the population under study (38.8%).5.There is a need to intensify actions aimed at fighting smoking, especially among minors, and to provide comprehensive help to individuals who want to give up that addiction.